The clinical spectrum and antibiotic sensitivity patterns of staphylococcal pyodermas in the community and hospital - Shireen Furtado; Ramesh M Bhat; B Rekha; D Sukumar; Ganesh H Kamath; Jacintha Martis; B Nandakishore (Wolters Kluwer Medknow Publications, 2014)
Context: The uncontrolled use of antibiotics has resulted in a relentless spread of multiresistant strains of Staphylococcus aureus. There are studies conducted in medical colleges in Chandigarh, Chennai, Mumbai and Vellore comparing pyodermas in the community and hospital setting based on clinical and bacteriological parameters. Aims: This study, conducted over 1½ years from March 2009 to August 2010, aimed at analyzing the clinical spectrum and antibiotic sensitivity pattern of community and hospital-associated (HA) staphylococcal pyoderma. It also assessed the prevalence of methicillin-resistant S. aureus (MRSA) in the community and hospital cohort settings. Subjects and Methods: The study comprised of 200 cases of staphylococcal pyodermas, derived from the community (150 cases) and hospital (50 cases). Patients were evaluated based on their clinical presentation; antibiotic susceptibility was tested using the Kirby-Bauer disk diffusion method. Statistical Analysis Used: Statistical significance between individual attributes between the community and HA staphylococcal pyoderma groups was analyzed using Chi-square test and mean differences using student's t-test. Results: Factors associated with community-associated (CA) pyodermas were young age (P = 0.0021), primary pyodermas, and involvement of extremities, while those with HA pyodermas were middle age, secondary pyodermas, and significantly increased body surface involvement (P = 0.041). Incidence of CA-MRSA was 11.3%, while that of HA-MRSA was 18%. Conclusions: A high level of resistance to first-line drugs such as penicillin, ciprofloxacin and cotrimoxazole was observed, more so in the hospital strain than in the community strain. S. aureus demonstrated good susceptibility to cephalosporins. Though the two strains of MRSA differed clinically, they showed 100% sensitivity to vancomycin and linezolid.